The Philippine Rondalla: A Gift Of Musical Heritage In A Migrant Context - Kim , Rockell (Penerbit Universiti Sains Malaysia (USM Press), 2013)
This paper reports on two recently developed contemporary rondallas outside the Philippines: one in Dansui, Taiwan and another in Queensland, Australia. The rondalla is a plucked-string ensemble which was brought to the Philippines from Spain in the late nineteenth century, not long before American intervention and the end of the Spanish era. This type of instrumental group was enthusiastically adopted in the Philippines and became an inexpensive and accessible medium for music education in schools. It has also become strongly connected to notions of Philippine national identity. Enjoying periodic resurgences within the Philippines, the characteristic, sparkling tremolo sound of rondalla instruments has an enduring place in the Philippine musical soundscape. This examination of rondallas in two diasporic locations confirms that the key concern for group founders is the transmission of culture of origin to secondgeneration Filipino migrants. In spite of a lack of funds and the scarcity of rondalla teachers, Filipinos have been able to reconstruct a treasured, musical heritage in their new homes. The paper also highlights the interesting contrast between the specific forms of multiculturalism which have arisen in Taiwan and Australia over the last few decades and have influenced the development of rondallas in each location. Recommendations for the rondalla's further development are offered, including the establishment of a freely downloadable database of scores and the creation of accessible educational multi-media materials for rondalla.